Revitalizing the Economy of Islamic Boarding School through Innovative Santripreneurs Towards Sustainable Economic Development - Fauzi, Ahmad; Sicha, Ainus; Atikoh, Nurul; Aina Salsabila, Isma; Rohmana, Devie Wianda (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Islamic boarding schools (pesantren) play a pivotal role not only as centers of Islamic education but also as potential drivers of community economic development. However, this potential often remains underutilized due to limitations in human resources, market access, and entrepreneurial innovation. In the context of globalization and sustainable development demands, pesantren are required to adopt more adaptive and creative strategies. One such approach is the santripreneur program, which empowers students (santri) with entrepreneurial skills grounded in Islamic values. This study aims to explore strategies for strengthening the economic resilience of pesantren through sustainable santripreneur initiatives and to examine their contribution to fostering community economic independence. This research employs a qualitative case study approach, utilizing observation, interviews, documentation, and literature review. Data were analyzed using the Miles, Huberman, and Saldana model, including data condensation, display, and conclusion drawing. The findings reveal that Wali Songo Ngabar Islamic Boarding School has successfully revitalized its economic system through santripreneurship. Various student-managed business units have been developed across sectors, including Islamic finance (BMT), retail and trade (minimarket and bottled water), production and creative industries (bakery, songkok, cleaning products, perfume), agriculture and livestock (farming, goat breeding, catering), and services (laundry, hotel, and meeting hall). These integrated business units form a sustainable economic ecosystem that enhances institutional financial independence while functioning as a practical entrepreneurship laboratory. Moreover, the program cultivates students’ character by fostering independence, creativity, teamwork, and an entrepreneurial spirit rooted in Islamic values, thus contributing meaningfully to broader community empowerment and sustainable development.